The Determinants Of SARS-CoV-2 Risk In Health Workers At Health Center Cimahi City: Control Case Study During Covid-19 - Ambar Dani syuhada; Ahmad, Nasir (Universitas Jenderal Achmad Yani Yogyakarta, 2025)
Background: Health workers at health centers in handling SARS-CoV-2 are a population with a high risk of infection. There were 39 health workers infected with SARS-CoV-2 in Cimahi City health centers during 2021.Objective: To determine risk factors for SARS-CoV-2 in health workers at the Cimahi City health center.Methods: This study was an analytic study with a case control design. The data collected were secondary data from health centers and Cimahi Health Office. Cases are people with SARS-CoV-2 infection diagnosed with SARS-CoV-2 based on PCR examination reports from the Cimahi Health Office in 2021. Controls are people who are not diagnosed with SARS-CoV-2 based on PCR examination reports from the Cimahi Health Office in 2021. The sample technique used total sampling of 37 cases and 37 controls with a ratio of 1: 1. Univariate data analysis to see frequency distribution and bivariate to see the causal relationship with the Chi-square test. Results: Completeness of using PPE is associated with the incidence of SARS-CoV-2. Age, gender, type of officer and comorbidities were not associated with the incidence of SARS-CoV-2 disease.Conclusion: health centers during the SARS-CoV-2 pandemic even though they have been given vaccines for immunity, it is hoped that health workers, both medical and non-medical, will continue to adhere to using PPE completely and correctly and of course always comply with health protocols.